(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The hair- and pore-pattern of caterpillars from the pine processionary moth Thaumetopoea pityocampa (Den. & Schiff.) was investigated by light and REM microscopic methods and the results were compared with the Ditrysia-type. The primary pattern of the cranial range shows clearly differences to the Ditrysia-scheme.